2002
DOI: 10.1002/1521-3773(20021018)41:20<3897::aid-anie3897>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Naphtho[1,8-b,c]phosphete and 1,2-Diphosphaacenaphthene from the Reaction of 1,8-Dilithionaphthalene with RPCl2

Abstract: Strained rings and metal insertions: The product of the reaction between 1,8‐dilithionaphthalene and RPCl2 differs depending on the R group on the phosphorus atom. PhPCl2 gave (PhP)2‐peri‐bridged naphthalene, while iPr2NPCl2 gave the iPr2‐bridged compound (see scheme). The reactivity of the new compounds with transition‐metal complexes is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…X-ray structures of 3a [7], 3b, and 4-6, and 7 were illustrated in Figs. 1 and 2, respectively, with numbering schemes adopted.…”
Section: Molecular Structuresmentioning
confidence: 99%
See 4 more Smart Citations
“…X-ray structures of 3a [7], 3b, and 4-6, and 7 were illustrated in Figs. 1 and 2, respectively, with numbering schemes adopted.…”
Section: Molecular Structuresmentioning
confidence: 99%
“…On the other hand, several research groups and we reported that a low valent transition metal such as a zerovalent platinum complex reacts with a strained phosphaheterocyle coordinating to a metal fragment to give a ring-expanded product with a platinum fragment inserted into a P-C bond [14,15]. Thus, 7 in which 3a is coordinating to a W(CO) 5 fragment was allowed to react with Pt(PPh 3 ) 4 [7]. 31 The two signals at 21 and 29 ppm could be assigned to PPh 3 ligands coordinating to the platinum and tungsten centers, respectively, whereas the signal at 88 ppm was assigned to the phosphorus moiety derived from 7.…”
Section: Ring-opening Reactionmentioning
confidence: 99%
See 3 more Smart Citations